2019
DOI: 10.1039/c9cp01128e
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme–luteolin binding: molecular insights into the complexation process and the inhibitory effects of luteolin towards protein modification

Abstract: Luteolin shows inhibitory effects towards fibrillation and d-ribose mediated glycation of HEWL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 106 publications
1
25
0
Order By: Relevance
“…This could occur through various molecular interactions such as collision quenching, ground‐state complex formation, excited state reactions, or rearrangements and excited state energy transfer from donor to acceptor molecules. [ 31,52 ] These interaction processes are classified as static quenching or dynamic quenching and can be identified using different studies such as temperature variation studies, viscosity, ground‐state complex formation, or precisely by executing the excited state lifetime measurements of protein and its complexes.…”
Section: Resultsmentioning
confidence: 99%
“…This could occur through various molecular interactions such as collision quenching, ground‐state complex formation, excited state reactions, or rearrangements and excited state energy transfer from donor to acceptor molecules. [ 31,52 ] These interaction processes are classified as static quenching or dynamic quenching and can be identified using different studies such as temperature variation studies, viscosity, ground‐state complex formation, or precisely by executing the excited state lifetime measurements of protein and its complexes.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Lysozyme is a small globular protein consisting of 129 amino acid residues, which comprise six tryptophan (Trp) residues, three tyrosine residues, and four disulfide bonds (Scheme 1a). 18,19 It has already been reported that the tryptophan residues W62 and W108 are responsible for the intrinsic fluorescence in Lyz. 2,7,18,20 Lyz can hydrolyze β-1,4-glycosidic linkages between N-acetylmuramic acid and N-acetyl glucosamine present in the peptidoglycan cell wall of bacteria, leading to bacterial cell lyses.…”
Section: Introductionmentioning
confidence: 99%
“…EPR, the 4′-epimer of Doxorubicin, displayed a similar tumor response during clinical trials of its application to breast cancer and the therapeutic effects . Hence, these properties of EPR are important as they have direct consequences in clinical research. , Lysozyme is a small globular protein consisting of 129 amino acid residues, which comprise six tryptophan (Trp) residues, three tyrosine residues, and four disulfide bonds (Scheme a). , It has already been reported that the tryptophan residues W62 and W108 are responsible for the intrinsic fluorescence in Lyz. ,,, Lyz can hydrolyze β-1,4-glycosidic linkages between N -acetylmuramic acid and N -acetyl glucosamine present in the peptidoglycan cell wall of bacteria, leading to bacterial cell lyses . The protein consists of two domains, namely α-domain (mainly comprising the α-helix) and β-domain (mainly comprising the β-sheet). , The substrate binding site (also known as “cleft”) is enclosed by these two domains .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysozyme exhibits diverse pharmacological properties like anti-bacterial, anti-cancer, anti-viral, anti-septic, and anti-inflammatory. It is also known to bind reversibly with small molecules and has been reported to be used as a carrier in drug delivery [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%